The role of NETosis in enhancing of atherosclerosis: Role of NETosis in enhancing of atherosclerosis - Blagov, Alexander V.; Churov, Alexey V.; Starodubtseva, Irina A.; Beloyartsev, Dmitry F.; Kovyanova, Tatiana I.; Pecherina, Tamara; Sukhorukov, Vasily N.; Orekhov, Alexander (Cellular and Molecular Biology, 2024)
Activated neutrophils release neutrophil extracellular traps (NETs), complex structures composed of extracellular genetic material and proteins sourced from the nucleus, granules, and cytoplasm in response to pathogenic inflammatory conditions. These NETs play a crucial role in the host’s innate immune defense against invasive infections. Notably, in conditions like atherosclerosis, these extracellular formations can also be elicited by inflammatory stimuli such as lipids, prothrombotic factors, platelet aggregation, or proinflammatory cytokines. NETs have been identified on the inner arterial walls in cardiovascular disease states. By promoting inflammation through NETosis-mediated cell adhesion processes and exerting cytotoxic effects leading to cellular dysfunction and tissue damage, NETs contribute to the pathogenesis of inflammatory conditions.